Revisiting nitrite sensitized photolysis for micropollutants removal: overlooked oxidative mechanisms of reactive nitrogen species and their dual role in byproduct toxicity - Zhilin Zhang; Sicheng Gong; Yiqi Liu; Qingyang Jiang; Zhongyue Sun; Wei Zhuang; Junhao Lin; Jiawei Liu; Zhichao Liu; Tonghao Yuan; Jun Shi; Huiping Deng (Water Research, 2026)

Optimization of the Multi-Channel Surface Electrogram Acquisition for Noninvasive Uterine Electrophysiology Imaging - Hansong Gao; Sicheng Wang; Yiqi Lin; Meng Jiang; Yuelin Li; Qiuchang Sun; Zichao Wen; Yong Wang (Annals of Biomedical Engineering, 2026)
Purpose The goal of optimizing electrogram acquisition in electrophysiology imaging is to minimize the number of electrodes used, determine their optimal placement, and ensure accurate imaging. Methods We quantitatively evaluated the impact of the electrode number and placement on the accuracy of human uterine peristalsis imaging (UPI) using adapted minimum nonzero eigenvalue pursuit (MNEP), adapted maximal projection on minimum eigenspace (MPME), and a distance-based baseline method. Specifically, we assessed the accuracy of the uterine surface electrogram imaged by UPI while maintaining the original 128-electrode UPI placement as a constraint. Subsequently, we expanded our analysis to the entire body surface of the subjects, removing the constraint of the initial UPI electrode placement to explore a generalized optimized electrode placement strategy. Results The MPME method demonstrated superior performance compared to other approaches under both constrained and unconstrained optimization. For UPI, the optimal electrode configuration should prioritize a dense concentration of electrodes on the lower abdomen, close to the uterus, where the most informative bioelectrical signals are captured. At the same time, it is important to maintain a distribution of electrodes along the edges of the upper abdominal, lateral sides, and posterior regions. This spatial distribution preserves the geometric contour of the torso and supports comprehensive, multi-angle observation of uterine electrical activity. By combining signal fidelity with spatial coverage, this balanced placement strategy enhances the UPI accuracy. Conclusions The adapted MPME method guided a novel electrode placement strategy for electrophysiological imaging, achieving substantial improvements in imaging accuracy while reducing system complexity and cost.

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

NF-κB modulates ROS/JNK signaling to attenuate apoptosis in largemouth bass hepatocytes during recovery from heat stress - Wenjia Mao; Genrong Zhang; Sicheng Liang; Yi Sun; Zijie Lin; Qufei Ling (Journal of Thermal Biology, 2026)

Soil respiration and crop biomass components were influenced by eight-year warming and straw retention practices - Shutao Chen; Miaomiao Zhang; Sicheng Ding; Xuewen Yao; Zhaohui Wang; Lin Sang; Zhenghua Hu (Journal of Soils and Sediments, 2026)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Multi-scale quantitative analysis of grotto sandstone degradation considering inorganic salt phase transitions - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Zihua Xiong; Siwei Jiang; Gang Zhao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Prefabricated building policy and low-carbon transformation of China’s construction industry - Jianshuang Fan; Yasai Liu; Lin Zhou; Kairun Zhao; Sicheng Cai (Energy and Buildings, 2025)

Elucidating reaction characteristics of reactive radicals in the UV/chlorine systems: Thermodynamic behavior and dynamic electron distribution - Zhilin Zhang; Jiawei Liu; Junhao Lin; Sicheng Gong; Ling Li; Jia Liu; Qingyang Jiang; Zhongyue Sun; Lei Ding; Jun Shi; Huiping Deng (Chemical Engineering Journal, 2025)

Oleic acid inhibits the proliferation, invasion, and migration of tongue squamous cell carcinoma cells under high glucose conditions through S100A9-HK2/PKM2-SOD2 signaling pathway - Yujie Ma; Runqiang Liu; Juan Zhan; Yihan Lai; Sicheng Li; Wei Wang; Yisen Shao; Lin Jiang (Tissue and Cell, 2025)

Scalable synthesis of anatase TiO2 nano-in-micro spheres for hybrid sodium-ion capacitors - Zerui Yan; Sicheng Fan; Xia Zou; Qinyao Jiang; Dafu Tang; Kun Lan; Jiaxin Li; Yingbin Lin; Zhigao Huang; Dong-liang Peng; Qiulong Wei (Chemical Engineering Journal, 2025)

Interfacial engineering of Bi3.64Mo0.36O6.55/Ti3C2 Schottky junctions based on work function for efficient photoexcitation-assisted degradation of antibiotics - Jiawei Liu; Jia Liu; Zhilin Zhang; Junhao Lin; ZiZhen Wu; Qingyang Jiang; Sicheng Gong; Jun Shi; Huiping Deng (Journal of Hazardous Materials, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Embryonic temperature influences transcriptomic and methylation profiles in the liver of juvenile largemouth bass - Zijie Lin; Sicheng Liang; Yekai Wei; Zhiying Cai; Genrong Zhang; Qufei Ling (Journal of Thermal Biology, 2025)

Cross-Scale Quantitative and Qualitative Study of Grotto Sandstone Under Salt Weathering - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Kaiqiang Zhang; Yu Lei; Siwei Jiang; Huili Chen; Gang Zhao; Xuemei Feng (Rock Mechanics and Rock Engineering, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Bio-based and fireproof radiative cooling aerogel film: Achieving higher sustainability and safety - Wei Cai; Bicheng Lin; Liangyuan Qi; Tianyang Cui; Zhaoxin Li; Junling Wang; Sicheng Li; Chengfei Cao; Mohammad Ziaur Rahman; Xin Hu; Rujun Yu; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

A novel creep contact model for rock and its implement in discrete element simulation - Wengang Zhang; Sicheng Lin; Luqi Wang; Lin Wang; Xiang Jiang; Shuo Wang (Computers and Geotechnics, 2024)

Incorporating copper-based nanosheets into an injectable self-healing hydrogel enables superb repair of infected diabetic wound - Dingqi Xie; Chuan Hu; Chao Jiang; Jiechao Xia; Lin Ye; Yang Jin; Sicheng Jiang; Yinwen Ji; Zhengduo Zhang; Honghai Song; Yutao Zhu; Pan Tang; et al. (Chemical Engineering Journal, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Designing functionalized graphene-stitched-SiC/fluoropolymer novel composite coating with excellent corrosion resistance and hydrogen diffusion barrier properties - Sicheng Yuan; Kun Li; Yue Sun; Chang Cong; Yaran Liu; Dan Lin; Luchao Pei; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

A multifunctional and long-term waterborne anti-corrosion coating with excellent ‘hexagonal warrior’ properties - Luchao Pei; Dan Lin; Sicheng Yuan; Renjie Lu; Ziheng Bai; Yue Sun; Yanji Zhu; Yuanxu Jiang; Jiajun Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

A smart composite coating with photothermal response, anti-UV and anti-corrosion properties - Yue Sun; Sicheng Yuan; Weihao Fan; Dan Lin; Kun Zhang; Ziheng Bai; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

How rainfalls influence urban traffic congestion and its associated economic losses at present and in future: taking cities in the Beijing-Tianjin-Hebei region, China for example? - Yi Zhou; Sicheng Mao; Haile Zhao; Guoliang Zhang; Xin Chen; Yuling Jin; Lin Xu; Zhihua Pan; Pingli An; Fei Lun (Theoretical and Applied Climatology, 2022)

Effects of 7 Years of Warming and Straw Application on Soil Bacterial, Fungal, and Archaeal Community Compositions and Diversities in a Crop Field - Miaomiao Zhang; Shutao Chen; Sicheng Ding; Xuewen Yao; Zhaohui Wang; Lin Sang (Journal of Soil Science and Plant Nutrition, 2022)